Pressure‐Induced Metallization of Lead‐Free Halide Double Perovskite (NH4)2PtI6. Issue 28 (15th August 2022) - Wang, Jiaxiang; Wang, Lingrui; Li, Yuqiang; Fu, Ruijing; Feng, Youjia; Chang, Duanhua; Yuan, Yifang; Gao, Han; Jiang, Sheng; Wang, Fei; Guo, Er‐jia; Cheng, Jinguang; et al.
Abstract: Metallization has recently garnered significant interest due to its ability to greatly facilitate chemical reactions and dramatically change the properties of materials. Materials displaying metallization under low pressure are highly desired for understanding their potential properties. In this work, the effects of the pressure on the structural and electronic properties of lead‐free halide double perovskite (NH4 )2 PtI6 are investigated systematically. Remarkably, an unprecedented bandgap narrowing down to the Shockley–Queisser limit is observed at a very low pressure of 0.12 GPa, showing great promise in optoelectronic applications. More interestingly, the metallization of (NH4 )2 PtI6 is initiated at 14.2 GPa, the lowest metallization pressure ever reported in halide perovskites, which is related to the continuous increase in the overlap between the valence and conduction band of I 5p orbital. Its structural evolution upon compression before the metallic transition is also tracked, from cubic Fm‐ 3 m to tetragonal P 4/ mnc and then to monoclinic C 2/ c phase, which is mainly associated with the rotation and distortions within the [PtI6 ] 2– octahedra. These findings represent a significant step toward revealing the structure–property relationships of (NH4 )2 PtI6, and also prove that high‐pressure technique is an efficient tool to design and realize superior optoelectronic materials. Abstract : An unprecedented bandgap narrowing of lead‐free halide double perovskite (NH4 )2 PtI6 down to the Shockley–Queisser limit is observed at a very low pressure of 0.12 GPa. More importantly, the lowest metallization pressure (14.2 GPa) is achieved ever reported in halide perovskites.